Does The Implementation of enterprise Resources Planning Moderates The Relationship Between performance and Profit Growth ? - Achyani, Fatchan; -, Zulfikar; Khoir, Jundi Abdul (JIFA (Journal of Islamic Finance and Accounting), 2021)
In theory, the application or implementation of an integrated system such as an enterprise resource planning system will further reduce sales, general and administrative expenses due to the effectiveness and efficiency of the workforce after the implementation of the enterprise resource planning system. However, the high costs and the risk of failure, the selection of ERP products must be right on target and can increase profits. In the study of three independent variables, the independent variables are Inventory Turnover (ITO), Earning Power (EP) and ERP moderation with one independent variable, namely profit growth. The sample used was 190 observation samples, the study used Pooled Least Square regression to analyze the impact of ERP implementation moderation on the relationship between company performance and profit growth listed on the Indonesia Stock Exchange for the period 2006 to 2018. The results of the analysis state that ERP implementation, Net Profit Margin (NPM), Inventory Turnover (ITO), earning power (EP), and ERP moderation simultaneously have a positive and significant effect on profit growth. Partially Inventory turnover, earning power, and ERP moderation variables on earning power have a positive effect on profit growth. Meanwhile, the moderate variable ERP on inventory turnover has no significant effect on profit growth.Keywords s: ERP, Inventory turnover, Earning power, Earning Growth